Preliminary study on cryopreservation of Dendrobium Bobby Messina protocorm- like bodies by vitrification - James Antony, Jessica Jeyanthi; Chan, Lai Keng; Rathinam, Xavier; Sinniah, Uma Rani; Subramaniam, Sreeramanan (Academic Journals, 2010)
Protocorm-like bodies of Dendrobium Bobby Messina were cryopreserved by vitrification method. In this study, protocorm-like bodies (PLBs) with the size range of 1-2 and 3-4 mm were selected from 4 weeks old culture, pretreated with half strength semi-solid Murashige and Skoog (MS) media supplemented with 0.5 M sucrose at 25°C for 24 h. Pretreated PLBs were then treated with a mixture of 2 M glycerol and 0.4 M sucrose supplemented with half strength liquid MS media at 25°C for 20 min. Osmoprotected PLBs were then dehydrated with plant vitrification solution 2 at 0°C for 20 min before storage in liquid nitrogen. After rapid warming in water bath at 40°C for 90 s, the PLBs were washed with half strength liquid MS media supplemented with 1.2 M sucrose and then cultured on half strength semi-solid MS media supplemented with 2% sucrose without the presence of any growth regulators. Survival of the cryopreserved PLBs was assessed based on triphenyl tetrazoliumchloride (TTC) spectrophotometrical analysis. The PLBs with 3-4 mm size range showed better viability comparative to size range 1-2 mm for both cryopreserved and non-cryopreserved PLBs. The best pretreatment concentration used in pretreatment media was 0.6 M sucrose and 1.2 M sorbitol, respectively.